KINERJA PEMERINTAH DESA DI DESA KAMARORA B KECAMATAN NOKILALAKI KABUPATEN SIGI - Ntee, Wiliam Rodolfo; Djaelangkara, Rizali; Labiro, Richard F. (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
His research aims to determine the performance of the Village Government in Kamarora B Village, Nokilalaki District, Sigi Regency. The research method used is Qualitative Descriptive, namely providing an overview of the phenomenon or focus of the problem being researched which occurs at the research location according to existing facts. The data collection techniques used were observation, in-depth informant interviews and documentation to collect the required data in the form of primary and secondary data. Meanwhile, there were 7 informants in this study, namely 3 people from the Kamarora B Village Government, 1 person from the Village Consultative Body, and 3 people from the Kamarora B Village Community. The theory used in this research is Agus Dwiyanto's theory where there are five indicators used In measuring the performance of the Village Government in Kamarora B Village, Nokilalaki District, Sigi Regency, the five indicators are Productivity, Service Quality, Responsiveness, Responsiveness and Accountability. Based on the research results, it shows that the performance of the Village Government in Kamarora B Village, Nokilalaki District, Sigi Regency, in general, its implementation is not optimal, can be seen in the Productivity Indicator, namely the use of village government time is still less than optimal, as evidenced by the development programmed by the Village Government in 2024 has not been carried out and there is a decline the amount of development realized by the Village Government between 2023 and 2024. Accountability Indicators can be seen that the Village Government is not fair in allocating development to each hamlet, while the Service Quality, Responsiveness and Responsibility Indicators are quite good in their implementation by the Village Government.